Bostadsgården - Kjellberg, Emelie (2009)
This candidate essay is built on literature studies and discusses the meaning of the residential yard along with what you, as a landscape architect, should think about when you are designing functional residential yards. To do this I found it necessary to figure out what it is that makes people step outside their own apartment and out into the city’s public places. The reasons for this are numerous and many times individually affected. Something that plays a role in people’s outdoor life and prevents them from spending time outside is the lack of time, the technique of today and the feeling off insecurity. The thing that makes us want to spend more time outside our home is the knowledge that it has a positive effect on our health. What does the residential yard mean to people today? The residential yard could be the first thing you set your foot onto when you step outside your home and out into the outdoor environment. It is neither as private as the garden, nor as public as a square or a park – it is a half private room in the townscape dedicated to the people living on the yard. A functional yard live up to four different roles in the every day life of people: a near housing environment, a playing field, a social arena and a view. The design of the outdoor environment plays, to some extent, a role but many times a functional residential yard depends on the relations between the people living there and the spaciousness. By being a social arena the residential yard and its outdoor environment have a key role in the development and maintaining of the social connection between neighbours. It gives the inmates of the house an opportunity to maintain the “weak ties” to their neighbours – they get a pleasant first contact – and acts as a second living room where the everyday life has a chance to move outside during favorable weather. Further more the residential yard is an important place to the children and as a playing field. Along with the role as a view the residential yard should make the passive users feel as participants in the life on the yard. In addition to this the residential yard can be divided into different zones: public, half public, half private and private. These zones, together with the physical environment and the four roles, create a good starting point for a functional residential yard. Besides the literature studies I have also done an analysis of my own residential yard which is based on how the outdoor environment of the residential yard is regarded through the physical environment, the four roles and the territorial zoning. The conclusion I found was that there is noting like ”the bestresidential yard” nor is there just one single truth on how to design a functional residential yard – there are many! If a residential yard is to function it is an absolute condition that the foundation is solid and that it can stand the test of time. How this is expressed is up to the people who live and use the residential yard to decide.